2022
DOI: 10.1002/alr.23037
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic differences between adult and pediatric patients with chronic rhinosinusitis

Abstract: Background Adult and pediatric patients with chronic rhinosinusitis (CRS) may have differing philosophies in therapeutic management. Few studies have examined sinonasal tissue‐level comparisons of these groups. This study examines histopathologic differences between children and adults with CRS, with the goal of understanding disease pathogenesis and optimizing medical management for both populations. Methods In a retrospective cohort of CRS patients who underwent functional endoscopic sinus surgery (FESS), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…A second disease control was selected that contained idiopathic CRSsNP because the typical PCD‐related CRS has significant edema and mucus but does not result in polyp formation. The SHR findings in our CRSsNP cohort resembled those reported in larger sample size by Brown et al., 6,7 which indicated a none to mild degree of inflammation, absence of neutrophil infiltration, absence of mucosal ulceration, absence of squamous metaplasia, and minimal fibrosis.…”
Section: Discussionsupporting
confidence: 89%
“…A second disease control was selected that contained idiopathic CRSsNP because the typical PCD‐related CRS has significant edema and mucus but does not result in polyp formation. The SHR findings in our CRSsNP cohort resembled those reported in larger sample size by Brown et al., 6,7 which indicated a none to mild degree of inflammation, absence of neutrophil infiltration, absence of mucosal ulceration, absence of squamous metaplasia, and minimal fibrosis.…”
Section: Discussionsupporting
confidence: 89%
“…. Brown et al recently reported that the majority (57.8%) of paediatric CRS cases had a lymphocyte-predominant inflammatory background, whereas the majority (66.5%) of adult CRS had a lymphoplasmacytic-predominant inflammatory background (26) . Differences in age, ethnic groups, environmental area, and the presence of polyps may be attributed to the different mechanisms and immunopathologic features of CRSwNP in the paediatric population (10) .…”
Section: Discussionmentioning
confidence: 99%
“…Children exhibited significantly less tissue neutrophilia (12 vs. 29%), basement membrane thickening (44 vs. 70%), subepithelial oedema (30 vs. 61%), squamous metaplasia (4 vs. 22%), and eosinophil aggregates (4 vs. 23%). Unlike adults, the majority (58%) of children exhibited a lymphocyte-predominant inflammatory background [33].…”
Section: The Role Of Airway Inflammationmentioning
confidence: 99%